Study of Gas Laser Operation - Abdullo Nabiev Abduvoxidovich (Peerian Journals Publishing, 2022)
This article is mainly about gas lasers, optical base, screen, diffraction grating (round), rulers were used the purpose of writing this article is to study the structure and operation of a gas laser, to measure the wavelength of laser radiation using a diffraction type. Laser light is used in surgery to perform non-invasive incisions of tissues, because under its influence the edges of the cut tissue are welded to prevent capillary mining. Used in oncology to break down cancer cells. (Because the laser light is strongly absorbed in them).In ophthalmology, laser light is used to “weld” the iris, which is intensified, and to create microscopic holes in the sclera to drain the fluid inside the eye to treat glaucoma.
Keywords: Gas laser; optical base; screen; diffraction grating